Assessment of the Evolution in Velocity of Two Debris‐Covered Valley Glaciers in Nepal and New Zealand. Issue 4 (10th September 2015) - Haritashya, Umesh K.; Pleasants, Mark S.; Copland, Luke
ABSTRACT: Feature tracking of orthorectified pairs of Advanced Spaceborne Thermal Emission and Reflection Radiometer satellite images is used to calculate velocities for the Tasman Glacier, New Zealand (2002–2014) and the Khumbu Glacier, Nepal (2001–2008). Velocities in the middle and upper ablation zones of both glaciers show a long‐term decrease of ∼10–20%, while the terminus of Khumbu Glacier has remained near stagnation throughout the study period. In contrast, there has been a recent acceleration of the lower terminus of Tasman Glacier, from ∼5 m a –1 in 2002 to 40 m a –1 in 2014. Both of these glaciers have an extensive supraglacial debris cover across their lower ablation regions, with the Khumbu Glacier terminating on land and the Tasman Glacier terminating in a proglacial lake. The rapid recent increase in velocity of the terminus of Tasman Glacier is closely correlated with the increase in size of its proglacial lake. These results indicate the complex dynamic changes that mountain valley glaciers may undergo in response to long‐term negative mass balance.